Botanicals Reduce Circulating Concentrations of Cholesterol and Triglycerides and Work Synergistically With Arachidonic Acid to Reduce Inflammatory Cytokines in Cats - Jewell, Dennis E.; Panickar, Kiran S. (Frontiers in Veterinary Science, 2021)
Forty Eight cats were used to measure the effects of feeding a traditional adult cat food supplemented with either arachidonic acid (ARA), a botanical mix (botanicals) or both on circulating factors of health and inflammatory cytokines. The cats were healthy adults (mean age, 3.0; range, 1.3-6.4 years). The adult cats were fed one of four foods (n = 12 per group) for 84 days: a traditional adult cat food (control, 0.05% ARA no added botanicals), or control food supplemented with arachidonic acid from liver (0.13% ARA when supplemented), control food supplemented with botanicals (green tea 0.5%, fenugreek 0.05%, and tulsi 0.003%), and control plus ARA (0.13% as fed) with botanicals (green tea 0.5%, fenugreek 0.05%, and tulsi 0.003%). Response variables were compared between treatments: initially, at 42 days and at 84 days (end of study). The measurements were standard complete blood counts and chemistries as well as the circulating cytokines. Botanical inclusion reduced circulating cholesterol and triglycerides while arachidonic acid increased their concentrations. The pro-inflammatory cytokines MCP-1, TNFα, SDF-1, Flt3L, IL-8, IL-12p40, IL-13, and IL-18 were all reduced in cats after consuming the ARA+botanicals food for 84 days with little reduction after consuming the other foods.